2018
DOI: 10.1109/tthz.2017.2771754
|View full text |Cite
|
Sign up to set email alerts
|

Optical System Design for Noncontact, Normal Incidence, THz Imaging of in vivo Human Cornea

Abstract: Reflection mode Terahertz (THz) imaging of corneal tissue water content (CTWC) is a proposed method for early, accurate detection and study of corneal diseases. Despite promising results from and cornea studies, interpretation of the reflectivity data is confounded by the contact between corneal tissue and dielectric windows used to flatten the imaging field. Herein, we present an optical design for non-contact THz imaging of cornea. A beam scanning methodology performs angular, normal incidence sweeps of a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…First, the field of view and target are well defined and display a high degree of uniformity. The geometry of the corneal surface is nearly spherical with a deviation in optical sag less than 1λ at 650 GHz [14]. Second, the target tissue thickness range can be measured a priori with a high degree of confidence and can be leveraged for deconvolving confounders in THz measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the field of view and target are well defined and display a high degree of uniformity. The geometry of the corneal surface is nearly spherical with a deviation in optical sag less than 1λ at 650 GHz [14]. Second, the target tissue thickness range can be measured a priori with a high degree of confidence and can be leveraged for deconvolving confounders in THz measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In related work [1] a non-contact, spherical scanning method for corneal imaging was introduced. The imaging method placed the corneal center of curvature (CoC) coincident with the focal point of an over-dimensioned (optics diameter ≫ individual collimated beam width) 90° off-axis parabolic (OAP) mirror, and scanned a collimated beam parallel to the axis of the mirror over the clear-aperture (CA) of the reflector (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In more complicated models, the diffusion of water could be considered in both the axial and the perpendicular directions. Future work will include expanding our model to include diffusion in the perpendicular directions and tracking it using spatial mapping of a spherical target, based on the experimental techniques in [16,17]. Furthermore, these results can be generalized to other tissue types or non-biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a sensitivity analysis, the study by Taylor et al showed the feasibility of THz imaging for cornea analysis by performing in vivo experiments on dehydrating healthy rabbit corneas through a mylar window [8]. More recently, efforts have been made to omit the need for an imaging window and develop a non-contact and normal-incidence THz imaging system designed specifically for in vivo and clinical assessment of corneal hydration [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The principle has been verified through the experimental results on ex-vivo porcine corneas [21,22] and in-vivo studies of rabbits [23] and humans [24]. By scanning a focused THz beam on volunteer's eye, Sung S., et al have obtained the reflectivity maps which represent spatial hydration distribution across human cornea [25][26][27]. But the reflected signal intensity is susceptible to all sorts of factors arising from instruments and samples, which will limit the accuracy and repeatability of measurements and make it challenging to calibrate the relation between CTWC and THz reflectivity.…”
Section: Introductionmentioning
confidence: 88%